The Narrative of Arthur Gordon Pym of Nantucket : Comprising the details of a mutiny and atrocious butchery on board the American brig Grampus, on her way to the South Seas, in the month of June, 1827. - Poe, Edgar Allan, 1809-1849 (Salt Lake City, UT : Project Gutenberg, 2016)
"The Narrative of Arthur Gordon Pym of Nantucket" by Edgar Allan Poe is a novel written and published in 1838. Young Arthur Gordon Pym stows away on a whaling ship, launching a harrowing maritime adventure filled with mutiny, shipwreck, and survival against impossible odds. As Pym journeys ever southward toward the Antarctic, his voyage grows increasingly strange and unsettling. Poe's only complete novel blends realistic seafaring detail with mysterious elements that defy easy explanation, culminating in an enigmatic ending near the South Pole. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Narrative_of_Arthur_Gordon_Pym_of_Nantucket
Release date is 2016-01-27
Produced by Ron Swanson
Keywords: Sea stories; Young men -- Fiction; Whaling ships -- Fiction; Stowaways -- Fiction